Traversing the Transcendent for Literary Exploration and Creative Translation of the Quran's First Revelatory Clot - Baharuddin Baharuddin; Lalu Jaswadi Putera (Universitas Pendidikan Mandalika, 2026)
Scholars and translators have a complicated and multi-faceted problem when attempting to translate the Quranic text, especially the opening lines of Surah Al-'Alaq (The Clot). With its foundation in the illustrious history of Islamic scholarship, this research delves into the methods used by three renowned translators, Marmaduke Pickthall, Yusuf Ali, and Mustafa Khattab, to bring these passages into English. This study explores the cultural, linguistic, and religious constraints involved in translating the Quran. It emphasizes the need of finding an equilibrium between literal and idiomatic translations, preserving the text's musicality and poetic qualities, and effectively conveying its profound spiritual and theological significance. The research examines the translators' strategies, drawing on theories of cultural and linguistic translation, to understand how they worked. These strategies included working with Islamic scholars, including multiple cultural viewpoints, and using explanatory notes. The results highlight the complex nature of translating the Quran and the constant attempts to improve translation methodologies via iterative review, technical developments, and multidisciplinary cooperation. The conclusion emphasizes the importance of maintaining the integrity of the Quranic text while making sure it's accessible and relevant to people all over the world.